The Combination of Phages and Faecal Microbiota Transplantation Can Effectively Treat Mouse Colitis Caused by Salmonella enterica Serovar Typhimurium - Wang, Xinwu; Xing, Yating; Ji, Yalu; Xi, Hengyu; Liu, Xiaohe; Yang, Li; Lei, Liancheng; Han, Wenyu; Gu, Jingmin (Frontiers in Microbiology, 2022)
Salmonella enterica serovar Typhimurium (S. Typhimurium) is one of the common causes of human colitis. In the present study, two lytic phages vB_SenS-EnJE1 and vB_SenS-EnJE6 were isolated and the therapeutic effect of the combination of phages and faecal microbiota transplantation (FMT) on S. Typhimurium-induced mouse colitis was investigated. The characteristics and genome analysis indicated that they are suitable phages for phage therapy. Results showed that vB_SenS-EnJE1 lysis 41/54 Salmonella strains of serotype O4, and vB_SenS-EnJE6 lysis 46/54 Salmonella strains of serotypes O4 and O9. Severe inflammatory symptoms and disruption of the intestinal barrier were observed in S. Typhimurium -induced colitis. Interestingly, compared with a single phage cocktail (Pc) or single FMT, the combination of Pc and FMT (PcFMT) completely removed S. Typhimurium after 72 h of treatment, and significantly improved pathological damage and restored the intestinal barrier. Furthermore, PcFMT effectively restored the intestinal microbial diversity, especially for Firmicutes/Bacteroidetes [predominantly bacterial phyla responsible for the production of short-chain fatty acids (SCFA)]. Additionally, we found that PcFMT treatment significantly increased the levels of SCFA. All these data indicated that the combination of phages and FMT possesses excellent therapeutic effects on S. Typhimurium -induced intestinal microbiota disorder diseases. Pc and FMT played roles in “eliminating pathogens” and “strengthening vital qi,” respectively. This study provides a new idea for the treatment of intestinal microbiota disorder diseases caused by specific bacterial infections.